Analisis Rasio-Rasio Dan Ukuran Keuangan, Prediksi Financial Distress, Dan Reaksi Investor - Mekani Vestari; Dessy Noor Farida (AKRUAL: JURNAL AKUNTANSI, 2013)
AbstractThe purpose of this paper is to investigate financial ratios and financial measurements that can predict financial distress. This study also examined investor reaction. To proved the effect for the long period this study not only examined the effect of independent variables per year to the prediction of financial distress, but also examined the average for five years.Using logistic regression the results showed that there are four financial ratios that can predict financial distress. Business risk and firm size is not proven to predict financial distress. Using Kruskall-Wallis test this study also proved that investors can predict financial distress.